STAGES OF TRANSPORT CORRIDOR DEVELOPMENT: MECHANISATION, ROBOTISATION, INTELLECTUALISATION AND DIGITALISATION PERSPECTIVES - Anokhov, I. V.; Rimskaya, O. N. (Strategičeskie rešeniâ i risk-menedžment (Online), 2022)
The aim of the article is to investigate the perspectives of transport corridors digitalisation. The subject of the study is rail freight transport. The authors use the Theory of Inventive Problem Solving (TIPS) methodology, which forms the basis of transport industry development stages: mechanisation, intellectualisation, robotisation (automation) and digitalisation. The transition from one stage to another is shown by the comparison between the two documents of significant importance for Eurasian transport: Agreement on International Goods Transport by Rail and Convention concerning International Carriage by Rail (CIM-COTIF). They are fundamentally different at the stages of mechanisation and robotisation that makes the digitisation of international transport corridors impracticable. The article clearly identifies the factors preventing digitalisation, as well as the ways of its neutralising. The research proves that a fully digitalised transport will represent an isolated system, aimed at meeting the most predicted part of human demands. The article presents the transport corridors digitalisation model. The authors state that modern transport is at the stage of automation and robotisation and has not yet approached digitalisation. The pipeline transport is the only transport mode that has closely reached the digital frontier. Railway transport also has favourable prerequisites and perspectives.